2021
DOI: 10.1177/23779608211017779
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Concerns of Women With High Risk Sexual Behaviors

Abstract: Introduction Expansion of reproductive health services and addressing its different aspects in national and international levels is an important step towards ensuring family and public health. Female sex workers are a vulnerable population that are exposed to high risk sexual behaviors and increased incidence of co-morbid health problems. This study aims to identify the concerns of women with high risk sexual behaviors. Clarifying different aspects of reproductive health and its problems in female sex workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Stigmatization seemed to have occurred mainly within client–provider interactions: eight of the studies reported incidents whereby sex workers experienced negative and differential treatment from staff members (Bick et al., 2017; Corneli et al., 2016; Ochako et al., 2018; Parmley et al., 2019; Rocha‐Jiménez et al., 2018; Ross et al., 2021; Wahed et al., 2017; Zenouzi et al., 2021). For example, a woman with high‐risk sexual behaviour from Iran said:
I don't like to go to health centers.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigmatization seemed to have occurred mainly within client–provider interactions: eight of the studies reported incidents whereby sex workers experienced negative and differential treatment from staff members (Bick et al., 2017; Corneli et al., 2016; Ochako et al., 2018; Parmley et al., 2019; Rocha‐Jiménez et al., 2018; Ross et al., 2021; Wahed et al., 2017; Zenouzi et al., 2021). For example, a woman with high‐risk sexual behaviour from Iran said:
I don't like to go to health centers.
…”
Section: Methodsmentioning
confidence: 99%
“…Once I asked a question from a mid‐wife, she looked to her colleagues and laughed at me; I will never go there again. (Zenouzi et al., 2021, p. 6)…”
Section: Methodsmentioning
confidence: 99%
“…To ensure better reproductive health outcomes, it's imperative for policymakers and healthcare providers to enhance access to reproductive healthcare services such as contraception, safe and legal abortion services, and family planning. In addition, instructional programs that promote sexual health, foster healthy relationships, and uphold reproductive rights have the potential to lessen unintended pregnancies and maximize health benefits from reproductive services [9].…”
Section: ) Reproductive Health Problemsmentioning
confidence: 99%